Role of testosterone in cognition and mobility of aging men. (31st August 2020) - Kaufman, Jean‐Marc; Lapauw, Bruno
Abstract: Background: Cognitive decline and impairment of physical performance and mobility are age‐related clinical problems with major negative impact on quality of life of elderly men. In how far the decline of testosterone production contributes to these problems in older men and whether testosterone therapy can contribute to slow down, prevent, or reverse their development remains subjects of debate. Objectives: This narrative review presents the current knowledge on association of sex steroid status with cognitive decline and impairment of physical function and mobility in elderly men and on the effects of testosterone therapy on cognition and on physical performance and mobility in elderly men. Materials and Method: The review is based on electronic database searches with primary focus on evidence from larger prospective observational studies and from controlled randomized trials, respectively. Results: In most observational studies, testosterone levels do not predict cognitive decline or development of Alzheimer's disease. In randomized trials, testosterone therapy did not significantly affect cognition in men with low or low‐to‐normal serum testosterone, regardless of whether they have preexisting cognitive impairment. Overall, observational data indicate that the usually moderate decline of androgen exposure in older men cannot fully account for the parallel decline of physical performance and mobility. Trials of testosterone therapy in older men with low or low‐normal serum testosterone, whether they were generally healthy or suffered from physical function impairments, either did not show any effect on mobility and physical performance or showed limited effects of uncertain clinical relevancy. Discussion and Conclusions: The whole of the evidence tends to downplay the role of sex steroid status in the decline of cognitive function and impairment of physical function and mobility in older men. Based on the available evidence, prevention or treatment of cognitive decline or of impairment of mobility and physical function are not valid indications for testosterone treatment in older men with low or low‐to‐normal serum testosterone levels.